Preparation method and application of antibacterial transparent nylon

Through the combination of cyclodextrin grafting technology and nano-scale metal ions, the compatibility and performance problems of nylon materials after the addition of antibacterial agents are solved, and the combination of high transparency and antibacterial properties is achieved, simplifying the production process and reducing environmental burden.

CN119286244AInactive Publication Date: 2025-01-10NINGBO JIANFENG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411337240.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, nylon materials have compatibility problems and reduced performance after adding antibacterial agents, and traditional methods lead to environmental pollution and are difficult to effectively apply in the field of transparent packaging.

Method used

Using cyclodextrin grafting technology, nylon material is combined with nano-scale metal ions. Through the molecular structure and hydrogen bond interaction of cyclodextrin, the crystallinity of nylon is inhibited and the uniform distribution of metal ions is achieved, thereby avoiding the coupling agent. Use improves the transparency and antibacterial properties of the material.

Benefits of technology

It realizes the combination of high transparency and excellent antibacterial properties of nylon materials, simplifies production processes, reduces costs and environmental burdens, and meets green manufacturing requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005058597420000151
    Figure BDA0005058597420000151
  • Figure BDA0005058597420000161
    Figure BDA0005058597420000161
Patent Text Reader

Abstract

The invention belongs to the technical field of high polymer material preparation, and relates to a preparation method and application of antibacterial transparent nylon. The preparation method comprises the following steps: adding nylon, a cross-linking agent and a catalyst into a modified cyclodextrin solution for grafting reaction to obtain cyclodextrin grafted nylon; adding the cyclodextrin grafted nylon into a nano-scale metal ion solution, and then filtering, washing and drying to obtain the antibacterial transparent nylon. According to the invention, a cyclodextrin grafting process is adopted to weaken the crystallinity of the nylon material so as to improve the light transmittance, and meanwhile, nano metal ions are successfully captured and fixed by virtue of a special structure of cyclodextrin, so that the material is endowed with excellent antibacterial performance and does not need to depend on a traditional coupling agent. It is ensured that the nylon material still has good overall performance after antibacterial modification, and a new thought is provided for developing an efficient compatibility technology and exploring and innovating a modification strategy for the nylon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material preparation, and relates to a preparation method of antibacterial transparent nylon and application thereof. Background Art

[0002] As we all know, nylon has been widely used due to its high strength, high toughness, wear resistance and impact resistance. Among the world's five major engineering plastics, its output and consumption are among the top, with an annual output of more than 8 million tons. Among them, nylon 6 (Polyamide 6 or PA6) is one of the most important and widely used varieties in the nylon series. The discovery and commercial production of nylon 6 marked the beginning of the synthetic fiber era. Since its advent in the 1930s, its application range has continued to expand, from the initial fiber to multiple fields of engineering plastics.

[0003] As the quality of human life continues to improve, health issues are becoming more and more important, and artificial fibers with antibacterial functions are also gaining more and more attention. Nylon 6 is a commonly used fiber product. In order to improve its antibacterial properties, people currently use nano-metal particles of silver and copper, titanium dioxide, antibacterial agents, etc. to fill it. However, this also brings up the problem of how to solve the compatibility of fillers and nylon materials.

[0004] In the existing technical solutions, nylon materials are given antibacterial properties mainly by adding inorganic antibacterial agents (such as inorganic silver-containing antibacterial agents, inorganic zinc-containing antibacterial agents, inorganic copper-containing antibacterial agents, etc.), rare earth silver antibacterial agents, titanium dioxide, organic-inorganic hybrid antibacterial agents, and silver plating. However, all these methods face the problem of how to solve the compatibility between the antibacterial agent and the nylon matrix, and the addition of inorganic antibacterial agents will also reduce the overall performance of the nylon material.

[0005] Qiqihar Beikun Synthetic Polymer Materials Co., Ltd. disclosed an antibacterial reinforced nylon material and its preparation method in Chinese patent CN103788645B. The method is mainly to first compound the rare earth silver inorganic antibacterial agent and titanium dioxide, make it into antibacterial masterbatch, and then prepare reinforced nylon, and finally evenly distribute the antibacterial masterbatch in the reinforced nylon of preparation number. This method ensures the tensile strength of nylon and realizes the uniform distribution of antibacterial agent, which improves the antibacterial effect, but because only physical mixing is adopted without secondary processing, the product will have defects in subsequent use. In addition, although the use of coupling agent solves the compatibility problem of inorganic antibacterial agent, it will inevitably affect the performance of nylon.

[0006] Xiamen Changsu Industrial Co., Ltd. disclosed a high barrier antibacterial nylon composite film and its preparation method in Chinese patent CN112318891A. The film includes a nylon substrate layer, an adhesive layer and a heat-sealing layer from top to bottom; the nylon substrate layer is a three-layer co-extruded biaxially stretched nylon film, the upper surface layer and the lower surface layer are composed of nylon resin, antibacterial agent and anti-adhesion agent, etc., the core layer is composed of nylon resin and nylon functional masterbatch, the antibacterial agent used in the invention is mainly an organic-inorganic hybrid antibacterial agent, the interior is a hyperbranched polyamide and a layered double metal hydroxide loaded with silver or copper metal salts, and the exterior is coated with polyvinyl alcohol and carboxymethyl chitosan. The invention has antibacterial properties while maintaining oxygen barrier properties, and is suitable for food and medical packaging, but the inherent low transparency of nylon limits its application in the field of transparent packaging. Similarly, this solution also requires the addition of a coupling agent due to the use of an inorganic antibacterial agent, which affects the performance of nylon, and waste is generated during the preparation of the antibacterial agent, and there will be problems such as environmental pollution.

[0007] Qingdao Yinyuansu Textile Technology Co., Ltd. discloses a method for preparing ultrafine silver-plated antibacterial nylon fiber in Chinese patent CN111005215A, which method includes: soaking nylon in an acetone aqueous solution, removing oil and dirt on the surface of the nylon fiber by ultrasonic washing, and then soaking it in a hydrochloric acid solution for surface activation, and then dissolving stannous chloride in the hydrochloric acid solution to sensitize the activated nylon fiber; then immersing it in a palladium chloride aqueous solution, and finally silver-plating the nylon fiber, preparing an oxidizing solution of silver nitrate aqueous solution and ammonia water, and a reducing solution of glucose solution and ethanol, and placing the treated nylon fiber therein, adjusting the pH value with sodium hydroxide, and inducing oxidation and reduction on the surface of the nylon fiber, thereby achieving the effect of silver plating. Although this method can make nylon fiber have an antibacterial effect and can be industrially produced continuously, a large amount of wastewater and pollutants are generated during the method, and environmental protection and subsequent treatment costs become significant problems.

[0008] Therefore, there is an urgent need to conduct research on efficient compatibility technology and explore innovative modification strategies for nylon 6 materials, aiming to balance and optimize the relationship between antibacterial properties and the overall performance of the material. This has become the core focus of research in this field. Summary of the invention

[0009] The invention aims at the deficiencies of nylon materials in the prior art and provides a preparation method of antibacterial transparent nylon and application thereof.

[0010] One object of the present invention is achieved by the following technical solutions:

[0011] A method for preparing antibacterial transparent nylon comprises the following steps:

[0012] (1) adding nylon, a crosslinking agent and a catalyst to a modified cyclodextrin solution to carry out a grafting reaction to obtain cyclodextrin-grafted nylon;

[0013] (2) Adding the cyclodextrin-grafted nylon into a nano-scale metal ion solution, and then filtering, washing, and drying to obtain the antibacterial transparent nylon.

[0014] Preferably, in step (1), the modified cyclodextrin solution is formed by dissolving the modified cyclodextrin in an alkaline aqueous solution, and the alkaline aqueous solution may be a sodium hydroxide aqueous solution, a potassium hydroxide aqueous solution, or the like; the concentration of the alkaline aqueous solution is 0.5 to 2.0 mol / L, and the concentration of the modified cyclodextrin is 0.1 to 1.0 g / mL.

[0015] Preferably, in step (1), the preparation method of modified cyclodextrin comprises the following steps: adding an acetonitrile solution of p-toluenesulfonyl chloride to an alkaline solution of cyclodextrin under stirring to produce a precipitate and adjust the pH, continuing to stir after the addition is complete, then neutralizing the reaction solution, and evaporating the filtrate obtained by suction to obtain modified cyclodextrin.

[0016] In the preparation method of the modified cyclodextrin, preferably, the cyclodextrin includes one or more of β-cyclodextrin, hydroxylated β-cyclodextrin, α-cyclodextrin, and γ-cyclodextrin.

[0017] In the preparation method of the modified cyclodextrin, preferably, the concentration of p-toluenesulfonyl chloride in acetonitrile is 0.1-1 mol / L.

[0018] In the preparation method of the modified cyclodextrin, preferably, the alkaline solution of cyclodextrin is formed by dissolving cyclodextrin in a sodium hydroxide solution, the concentration of the sodium hydroxide solution is 0.5-2.0 mol / L, and the concentration of the cyclodextrin is 0.1-1.0 g / mL.

[0019] In the preparation method of the modified cyclodextrin, preferably, the ratio of the alkaline solution of cyclodextrin to the acetonitrile solution of p-toluenesulfonyl chloride is (8-15):1.

[0020] In the preparation method of the modified cyclodextrin, preferably, an alkaline solution is used to adjust the pH to 12-14, and the alkaline solution includes one or more of ammonia water, potassium hydroxide, and sodium hydroxide.

[0021] In the preparation method of the modified cyclodextrin, preferably, the dropping is continued for 1 to 5 hours and then the stirring is continued for 1 to 5 hours.

[0022] In the preparation method of the modified cyclodextrin, preferably, an acidic solution is added to the reaction solution for neutralization, and the acidic solution includes one or more of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and carbonic acid.

[0023] Preferably, in step (1), the raw materials used include the following parts by weight: 8-20 parts of modified cyclodextrin, 85-92 parts of nylon, 0.1-1 part of cross-linking agent, and 0.1-1 part of catalyst.

[0024] Preferably, in step (1), the nylon includes one or more of nylon 6, nylon 66, nylon 11, nylon 12, nylon 610, nylon 612, nylon 1010 and nylon 46; more preferably, the nylon is nylon 6.

[0025] Preferably, in step (1), the cross-linking agent includes one or more of silicon dioxide, polyethylene glycol dimethacrylate (PEGDMA), methyl methacrylate (MMA), and ethylene glycol dimethacrylate (EGDMA).

[0026] Preferably, in step (1), the catalyst comprises one or more of aluminum oxide, titanium dioxide, copper oxide, iron oxide, and chromium oxide.

[0027] Preferably, in step (1), the grafting reaction temperature is 60 to 100° C. and the time is 60 to 100 minutes.

[0028] Preferably, in step (2), the nano-sized metal ion solution is an aqueous solution rich in nano-sized metal ions, with a concentration of (1000-8000) mg / L.

[0029] Preferably, in step (2), the nanoscale metal ions in the nanoscale metal ion solution include nanoscale silver ions or nanoscale copper ions, and the particle size is 1 to 100 nm.

[0030] Preferably, in step (2), the ratio of cyclodextrin-grafted nylon to nanoscale metal ion solution is (1-20) g: (50-1000) mL.

[0031] The second object of the present invention is achieved by the following technical solutions:

[0032] An antibacterial transparent nylon composite material comprises the following components in parts by weight: 90 to 100 parts of the antibacterial transparent nylon prepared by the above preparation method and 1 to 10 parts of an antioxidant.

[0033] Preferably, the antioxidant comprises a hindered phenol antioxidant and / or a phosphite antioxidant.

[0034] Preferably, the hindered phenol antioxidant includes one or more of antioxidant 1010, antioxidant 1098, antioxidant 1076, antioxidant 2246S, antioxidant 300, antioxidant 245, antioxidant 1790, and antioxidant GA-80.

[0035] Preferably, the phosphite antioxidant includes one or more of antioxidant 168, antioxidant 626, and antioxidant 618.

[0036] The third object of the present invention is achieved by the following technical solutions:

[0037] A method for preparing an antibacterial transparent nylon composite material, the preparation method comprising the following steps:

[0038] S1. Wash the antibacterial transparent nylon and dry it for later use;

[0039] S2, weighing the cleaned antibacterial transparent nylon and the antioxidant and mixing them evenly to obtain a mixture;

[0040] S3, feeding the mixture into a twin-screw extruder and granulating it through melt extrusion.

[0041] Preferably, in step S3, the mixture is fed into a twin-screw extruder through a feeding port, the motor frequency of the feeder is controlled to be 30-40 Hz, and the temperature of each temperature control zone is set to 220-250°C.

[0042] Further preferably, the twin-screw extruder includes 9 temperature control zones, and the temperature of temperature control zones 1 to 2 is set to 220-230°C, the temperature of temperature control zones 3 to 4 is set to 230-250°C, the temperature of temperature control zones 5 to 6 is set to 220-230°C, and the temperature of temperature control zones 7 to 9 is set to 220-250°C.

[0043] Further preferably, the twin-screw extruder has two vacuum ports, and the position of the vacuum ports is set after the shearing section in the barrel of the extruder. This means that after the material has undergone high-intensity shearing, mixing and melting, the physical changes have been completed when it reaches the vacuum port position. At this time, the residual gas (such as moisture, volatile solvents or other gases) in the material can be effectively removed by vacuuming, thereby improving the quality and performance of the final product, reducing bubbles, and improving density and surface finish.

[0044] Compared with the prior art, the present invention has the following beneficial effects:

[0045] 1. The present invention provides an antibacterial transparent nylon, which adopts the method of grafting nylon materials with cyclodextrin and utilizes the molecular structure characteristics of cyclodextrin. Its ring structure can be effectively inserted into the nylon molecular chain, and through the steric hindrance effect and hydrogen bond interaction, it interferes with and weakens the original strong hydrogen bond network structure of nylon and the orderliness of the crystal region. With the assistance of cross-linking agents and catalysts, this process can effectively inhibit the large-scale crystallization inside the nylon material, resulting in a significant decrease in crystallinity, which directly promotes the reduction of light scattering in the material, thereby greatly improving the light transmittance and transparency of the nylon material.

[0046] 2. The present invention provides an antibacterial transparent nylon, which further utilizes the strong tolerance of cyclodextrin molecular cavities to metal ions, and designs a strategy for cyclodextrin to capture nano-scale metallic silver particles. Nano-scale metal ions are precisely encapsulated in the molecular cavities of cyclodextrin, and then these cyclodextrin units carrying metal ions are grafted onto the nylon molecular chains. This chemical reaction pathway not only ensures the uniform distribution of metal ions in the nylon matrix and avoids aggregation, but also can successfully give nylon materials excellent antibacterial properties through the antibacterial effect of metal ions without the need for an external coupling agent.

[0047] 3. The present invention provides a method for preparing antibacterial transparent nylon, which adopts a cyclodextrin grafting process and the characteristics of efficient capture of metal ions, and abandons the coupling agent auxiliary means commonly used in the production of traditional antibacterial nylon. The absence of coupling agent assistance not only simplifies the production process and reduces the use of chemical additives, but also significantly reduces production costs; and it greatly reduces the potential burden on the environment, meeting the requirements of modern green manufacturing and sustainable development. The dual role of cyclodextrin not only protects the original properties of nylon materials, ensuring that its comprehensive performance after antibacterial modification is not damaged, but also sets a new benchmark for the development of environmentally friendly antibacterial materials, and provides innovative ideas for achieving a perfect combination of high performance and environmental friendliness. DETAILED DESCRIPTION

[0048] The technical solution of the present invention is further described below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to this application.

[0049] In the following examples and comparative examples:

[0050] The antioxidant is a composite antioxidant made by mixing the antioxidant Irganox1076 and the antioxidant Irgafos168 of BASF of Germany in a mass ratio of 95:5.

[0051] The nano-scale metallic silver ion solution adopts the polymer-specific nano-silver Ind5000 produced by Guangzhou Kejin Material Technology Co., Ltd.

[0052] Example 1

[0053] The preparation method of the antibacterial transparent nylon in this embodiment comprises the following steps:

[0054] (1) 5 g of β-cyclodextrin was added to 500 mL of sodium hydroxide aqueous solution (1.0 mol / L) to form a β-cyclodextrin-sodium hydroxide solution, which was stirred at a speed of 20 revolutions / s, and 50 mL of acetonitrile solution of p-toluenesulfonyl chloride (0.1 mol / L) was slowly added dropwise to the β-cyclodextrin-sodium hydroxide solution to produce a white precipitate. The pH was maintained at 13 with a NaOH solution, and the solution was added dropwise for 3 h and then stirred for 1 h. Then, HCl was added to the reaction solution to neutralize the unreacted NaOH, and the unreacted p-toluenesulfonyl chloride was removed by suction. The filtrate was evaporated using a rotary evaporator to obtain a white evaporation product, which was the modified cyclodextrin.

[0055] (2) 5 g of modified cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.0 mol / L), and then 20 g of PA6 particles, 0.5 g of silica and 0.3 g of alumina were added for grafting reaction at a reaction temperature of 100° C. for a reaction time of 60 min, followed by water washing, soap boiling and drying to obtain cyclodextrin-grafted nylon;

[0056] (3) 10 g of cyclodextrin-grafted nylon was added into 500 mL of nano-scale metallic silver ion solution (5000 mg / L, silver ion particle size was 25 nm), and then filtered, washed with water, and dried to obtain the antibacterial transparent nylon.

[0057] The preparation method of the antibacterial transparent nylon composite material of this embodiment comprises the following steps:

[0058] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0059] S2, weighing 99 parts of washed antibacterial transparent nylon and 1 part of antioxidant and mixing them evenly to obtain a mixture;

[0060] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, an antibacterial transparent nylon composite material, through melt extrusion and granulation.

[0061] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 230°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 220°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 230°C, and the temperature of temperature control zone 9 is 240°C.

[0062] Example 2

[0063] The preparation method of the antibacterial transparent nylon material of this embodiment comprises the following steps:

[0064] (1) 10 g of β-cyclodextrin was added to 500 mL of sodium hydroxide aqueous solution (1.2 mol / L) to form a β-cyclodextrin-sodium hydroxide solution, and the mixture was stirred at a speed of 20 revolutions / s. 50 mL of acetonitrile solution (0.1 mol / L) of p-toluenesulfonyl chloride was slowly added dropwise to the β-cyclodextrin-sodium hydroxide solution to produce a white precipitate. The pH value was maintained at 12.5 with a KOH solution, and the mixture was added dropwise for 3 h and then stirred for 1 h. HCl was then added to the reaction solution to neutralize the unreacted KOH, and the unreacted p-toluenesulfonyl chloride was removed by suction. The filtrate was evaporated using a rotary evaporator to obtain a white evaporation product, which was the modified cyclodextrin.

[0065] (2) 5 g of modified cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.0 mol / L sodium hydroxide concentration), and then 20 g of PA6 particles, 0.5 g of polyethylene glycol dimethacrylate and 0.3 g of titanium dioxide were added for grafting reaction at a reaction temperature of 60° C. for a reaction time of 100 min, followed by water washing, soap boiling and drying to obtain cyclodextrin-grafted nylon;

[0066] (3) 10 g of cyclodextrin-grafted nylon was added into 500 mL of nano-scale metallic silver ion solution (5000 mg / L, silver ion particle size was 25 nm), and then filtered, washed with water, and dried to obtain the antibacterial transparent nylon.

[0067] The preparation method of the antibacterial transparent nylon composite material of this embodiment comprises the following steps:

[0068] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0069] S2, weighing 100 parts of washed antibacterial transparent nylon and 1 part of antioxidant and mixing them evenly to obtain a mixture;

[0070] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, an antibacterial transparent nylon composite material, through melt extrusion and granulation.

[0071] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 225°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 235°C, the temperature of temperature control zone 4 is and 245°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 225°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 235°C, and the temperature of temperature control zone 9 is 245°C.

[0072] Example 3

[0073] The preparation method of the antibacterial transparent nylon in this embodiment comprises the following steps:

[0074] (1) 5 g of β-cyclodextrin was added to 500 mL of sodium hydroxide aqueous solution (1.5 mol / L) to form a β-cyclodextrin-sodium hydroxide solution, which was stirred at a speed of 15 rpm, and 50 mL of acetonitrile solution of p-toluenesulfonyl chloride was slowly added dropwise to the β-cyclodextrin-sodium hydroxide solution to produce a white precipitate. The pH value was maintained at 13 with a NaOH solution, and the addition was continued for 3 h and then stirred for 1 h. Then, HCl was added to the reaction solution to neutralize the unreacted NaOH, and the unreacted p-toluenesulfonyl chloride was removed by suction. The filtrate was evaporated by a rotary evaporator to obtain a white evaporation product, which was the modified cyclodextrin.

[0075] (2) 5 g of modified cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.5 mol / L sodium hydroxide concentration), and then 20PA6 particles, 0.5 g of methacrylate and 0.3 g of copper oxide were added for grafting reaction at a reaction temperature of 100° C. for a reaction time of 60 min, followed by water washing, soap boiling and drying to obtain cyclodextrin-grafted nylon;

[0076] (3) 10 g of cyclodextrin-grafted nylon was added into 500 mL of nano-scale metallic silver ion solution (5000 mg / L, silver ion particle size was 25 nm), and then filtered, washed with water, and dried to obtain the antibacterial transparent nylon.

[0077] The preparation method of the antibacterial transparent nylon composite material of this embodiment comprises the following steps:

[0078] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0079] S2, weighing 100 parts of washed antibacterial transparent nylon and 1 part of antioxidant and mixing them evenly to obtain a mixture;

[0080] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, an antibacterial transparent nylon composite material, through melt extrusion and granulation.

[0081] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 225°C, the temperature of temperature control zone 3 is 235°C, the temperature of temperature control zone 4 is and 245°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 225°C, the temperature of temperature control zone 7 is 230°C, the temperature of temperature control zone 8 is 240°C, and the temperature of temperature control zone 9 is 245°C.

[0082] Example 4

[0083] The preparation method of the antibacterial transparent nylon in this embodiment comprises the following steps:

[0084] (1) 3 g of β-cyclodextrin was added to 400 mL of sodium hydroxide aqueous solution (1.0 mol / L) to form a β-cyclodextrin-sodium hydroxide solution, which was stirred at a speed of 20 revolutions / s, and 50 mL of acetonitrile solution of p-toluenesulfonyl chloride was slowly added dropwise to the β-cyclodextrin-sodium hydroxide solution to produce a white precipitate. The pH value was maintained at 13 with an ammonia aqueous solution, and the addition was continued for 3 hours and then stirred for 1 hour. Then, HCl was added to the reaction solution to neutralize the unreacted NaOH and ammonia aqueous solution, and the unreacted p-toluenesulfonyl chloride was removed by suction filtration. The filtrate was evaporated by a rotary evaporator to obtain a white evaporation product, which was the modified cyclodextrin;

[0085] (2) 10 g of modified cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.5 mol / L sodium hydroxide), and then 20 g of PA6 particles, 0.5 g of ethylene glycol dimethacrylate and 0.3 g of iron oxide were added for grafting reaction at a reaction temperature of 100° C. for a reaction time of 60 min, followed by water washing, soap boiling and drying to obtain cyclodextrin-grafted nylon;

[0086] (3) 20 g of cyclodextrin-grafted nylon was added into 500 mL of nano-scale metallic silver ion solution (5000 mg / L, silver ion particle size was 25 nm), and then filtered, washed with water, and dried to obtain the antibacterial transparent nylon.

[0087] The preparation method of the antibacterial transparent nylon composite material of this embodiment comprises the following steps:

[0088] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0089] S2, weighing 100 parts of washed antibacterial transparent nylon and 3 parts of antioxidant and mixing them evenly to obtain a mixture;

[0090] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, an antibacterial transparent nylon composite material, through melt extrusion and granulation.

[0091] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 235°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 225°C, the temperature of temperature control zone 7 is 230°C, the temperature of temperature control zone 8 is 235°C, and the temperature of temperature control zone 9 is 240°C.

[0092] Comparative Example 1

[0093] The preparation method of the antibacterial transparent nylon in this comparative example is the same as that in Example 1.

[0094] The preparation method of the nylon composite material of this comparative example comprises the following steps:

[0095] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0096] S2, weighing 100 parts of washed antibacterial transparent nylon, 0.5 parts of rare earth silver inorganic antibacterial agent, 0.1 parts of silane coupling agent and 3 parts of antioxidant, and mixing them evenly to obtain a mixture;

[0097] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, nylon composite material, through melt extrusion and granulation.

[0098] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 230°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 220°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 230°C, and the temperature of temperature control zone 9 is 240°C.

[0099] Comparative Example 2

[0100] The preparation method of the antibacterial transparent nylon in this comparative example is the same as that in Example 1.

[0101] The preparation method of the nylon composite material of this comparative example comprises the following steps:

[0102] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0103] S2, weighing 99 parts of washed antibacterial transparent nylon, 1 part of rare earth silver inorganic antibacterial agent, 0.1 part of silane coupling agent and 2 parts of antioxidant and mixing them evenly to obtain a mixture;

[0104] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, nylon composite material, through melt extrusion and granulation.

[0105] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 230°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 220°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 230°C, and the temperature of temperature control zone 9 is 240°C.

[0106] Comparative Example 3

[0107] The preparation method of the antibacterial transparent nylon in this comparative example is the same as that in Example 1.

[0108] The preparation method of the nylon composite material of this comparative example comprises the following steps:

[0109] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0110] S2, weighing 99 parts of washed antibacterial transparent nylon, 1 part of organic-inorganic hybrid antibacterial agent (hyperbranched polyamide and layered double metal hydroxide loaded with silver metal salt inside, and polyvinyl alcohol and carboxymethyl chitosan coated outside), 0.1 part of silane coupling agent and 2 parts of antioxidant, and mixing them evenly to obtain a mixture;

[0111] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, nylon composite material, through melt extrusion and granulation.

[0112] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 230°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 220°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 230°C, and the temperature of temperature control zone 9 is 240°C.

[0113] Comparative Example 4

[0114] The preparation method of the antibacterial transparent nylon in this comparative example is the same as that in Example 1.

[0115] The preparation method of the nylon composite material of this comparative example comprises the following steps:

[0116] S1, washing the antibacterial transparent nylon prepared by the above preparation method, drying it and setting it aside;

[0117] S2, weighing 99 parts of washed antibacterial transparent nylon, 0.5 parts of organic-inorganic hybrid antibacterial agent (hyperbranched polyamide and layered double metal hydroxide loaded with silver metal salt inside, and polyvinyl alcohol and carboxymethyl chitosan coated outside), 0.1 parts of silane coupling agent and 3 parts of antioxidant, and mixing them evenly to obtain a mixture;

[0118] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, nylon composite material, through melt extrusion and granulation.

[0119] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 230°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 220°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 230°C, and the temperature of temperature control zone 9 is 240°C.

[0120] Comparative Example 5

[0121] The difference between this comparative example and Example 1 is that no cross-linking agent and catalyst are added in the preparation of nylon, and the rest is the same as Example 1.

[0122] The preparation method of nylon comprises the following steps:

[0123] (1) 5 g of β-cyclodextrin was added to 500 mL of sodium hydroxide aqueous solution (1.0 mol / L) to form a β-cyclodextrin-sodium hydroxide solution, which was stirred at a speed of 20 revolutions / s, and 50 mL of acetonitrile solution of p-toluenesulfonyl chloride (0.1 mol / L) was slowly added dropwise to the β-cyclodextrin-sodium hydroxide solution to produce a white precipitate. The pH was maintained at 13 with a NaOH solution, and the solution was added dropwise for 3 h and then stirred for 1 h. Then, HCl was added to the reaction solution to neutralize the unreacted NaOH, and the unreacted p-toluenesulfonyl chloride was removed by suction. The filtrate was evaporated using a rotary evaporator to obtain a white evaporation product, which was the modified cyclodextrin.

[0124] (2) 5 g of modified cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.0 mol / L), and then 20 g of PA6 particles were added for grafting reaction at a reaction temperature of 100° C. for a reaction time of 60 min, followed by water washing, soap boiling, and drying to obtain cyclodextrin-grafted nylon;

[0125] (3) 10 g of cyclodextrin-grafted nylon was added into 500 mL of nano-scale metallic silver ion solution (5000 mg / L, silver ion particle size was 25 nm), and then filtered, washed with water, and dried to obtain the antibacterial transparent nylon.

[0126] The preparation method of the nylon composite material in this comparative example is the same as that in Example 1.

[0127] Comparative Example 6

[0128] The difference between this comparative example and Example 1 is that the cyclodextrin is not modified in the preparation of nylon, and the cyclodextrin and nylon are directly blended. The rest is the same as Example 1.

[0129] The comparative example nylon preparation method comprises the following steps:

[0130] (1) 5 g of β-cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.0 mol / L), and then 20 g of PA6 particles, 0.5 g of silicon dioxide and 0.3 g of aluminum oxide were added and mixed evenly, and then washed with water, soaped and dried to obtain nylon containing cyclodextrin;

[0131] (2) 10 g of nylon containing cyclodextrin was added to 500 mL of nano-scale metallic silver ion solution (5000 mg / L, silver ion particle size was 25 nm), and then filtered, washed with water, and dried to obtain comparative example nylon.

[0132] The preparation method of the nylon composite material in this comparative example is the same as that in Example 1.

[0133] Comparative Example 7

[0134] The difference between this comparative example and Example 1 is that no nano-scale metallic silver ion solution is added in the preparation of nylon, and the rest is the same as Example 1.

[0135] The comparative example nylon preparation method comprises the following steps:

[0136] (1) 5 g of β-cyclodextrin was added to 500 mL of sodium hydroxide aqueous solution (1.0 mol / L) to form a β-cyclodextrin-sodium hydroxide solution, which was stirred at a speed of 20 revolutions / s, and 50 mL of acetonitrile solution of p-toluenesulfonyl chloride (0.1 mol / L) was slowly added dropwise to the β-cyclodextrin-sodium hydroxide solution to produce a white precipitate. The pH was maintained at 13 with a NaOH solution, and the solution was added dropwise for 3 h and then stirred for 1 h. Then, HCl was added to the reaction solution to neutralize the unreacted NaOH, and the unreacted p-toluenesulfonyl chloride was removed by suction. The filtrate was evaporated using a rotary evaporator to obtain a white evaporation product, which was the modified cyclodextrin.

[0137] (2) 5 g of modified cyclodextrin was dissolved in 500 mL of sodium hydroxide aqueous solution (1.0 mol / L), and then 20 g of PA6 particles, 0.5 g of silica and 0.3 g of alumina were added for grafting reaction at a reaction temperature of 100° C. for 60 min, followed by water washing, soap boiling and drying to obtain comparative nylon.

[0138] The preparation method of the nylon composite material in this comparative example is the same as that in Example 1.

[0139] Comparative Example 8

[0140] The difference between this comparative example and Example 1 is that the nylon composite material is prepared by using original PA6 and antioxidant, and the rest is the same as Example 1.

[0141] The preparation method of the nylon composite material of this comparative example comprises the following steps:

[0142] S1. Wash PA6 and dry it for later use;

[0143] S2, weigh 99 parts of washed PA6 and 1 part of antioxidant and mix them evenly to obtain a mixture;

[0144] S3. Feed the mixture into a twin-screw extruder through a feeding port, control the motor frequency of the feeder at 35 Hz, set the temperature of each zone at 220-250° C., and obtain the target product, an antibacterial transparent nylon composite material, through melt extrusion and granulation.

[0145] Specifically, in step S3, the twin-screw extruder includes 9 temperature control zones: the temperature of temperature control zone 1 is 220°C, the temperature of temperature control zone 2 is 230°C, the temperature of temperature control zone 3 is 230°C, the temperature of temperature control zone 4 is and 240°C, the temperature of temperature control zone 5 is 230°C, the temperature of temperature control zone 6 is 220°C, the temperature of temperature control zone 7 is 220°C, the temperature of temperature control zone 8 is 230°C, and the temperature of temperature control zone 9 is 240°C.

[0146] The nylon composite materials obtained in the examples and comparative examples were tested for IZOD notched impact strength, tensile strength, flexural strength, antibacterial properties and light transmittance, and the testing methods were as follows:

[0147] IZOD notched impact strength is measured in accordance with ISO 180;

[0148] The tensile strength is measured according to ISO 178;

[0149] The flexural strength is measured according to ISO 527;

[0150] The antibacterial property is determined in accordance with GB / T 31402-2015;

[0151] The transmittance is measured under D65-10 light source through a sample with a thickness of 4.0 mm.

[0152] The specific test results are shown in Table 1.

[0153] Table 1 Performance data of various embodiments and comparative examples

[0154]

[0155]

[0156] As shown in Table 1, it can be seen from Examples 1 to 4 and Comparative Example 8 that the antibacterial transparent nylon material prepared by the technical solution of the present invention not only ensures high light transmittance, but also exhibits excellent antibacterial performance. It is fully proved that in the process of cyclodextrin grafting nylon, the present invention weakens the crystallinity of the nylon material to improve the light transmittance, and successfully captures and fixes nano-scale metal ions with the help of the special structure of cyclodextrin, giving the material excellent antibacterial properties, without relying on traditional coupling agents, avoiding the risks of environmental pollution and material performance damage that may be caused by additional chemical additives.

[0157] It can be seen from comparative examples 1 to 7 that, without using the technical solution of the present invention, the specific embodiment is: when no cross-linking agent and catalyst are used in the raw material preparation of modified PA6 / when nylon particles and cyclodextrin are directly blended when preparing modified PA6, the prepared antibacterial transparent nylon material cannot achieve high light transmittance; when the step of cyclodextrin capturing metal ions is not performed, the antibacterial nylon material prepared by directly using cyclodextrin grafted PA6 has good light transmittance, but the antibacterial performance of the material is obviously insufficient. This illustrates the irreplaceable nature of the cyclodextrin grafting and metal ion capture mechanism in the present invention and its decisive influence on the comprehensive performance of the final product.

[0158] The various aspects, embodiments, and features of the present invention should be considered to be illustrative in all aspects and not limiting of the present invention, the scope of which is defined solely by the claims. Other embodiments, modifications, and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0159] In the preparation method of the present invention, the order of each step is not limited to the order listed. For those skilled in the art, without creative work, the order of each step is also within the protection scope of the present invention. In addition, two or more steps or actions can be performed simultaneously.

[0160] Finally, it should be noted that the specific embodiments described herein are merely examples of the present invention, and are not intended to limit the implementation methods of the present invention. A person skilled in the art of the present invention may make various modifications or supplements to the specific embodiments described, or replace them in a similar manner. It is not necessary and impossible to provide all examples of all implementation methods here. However, these obvious changes or modifications derived from the essential spirit of the present invention still fall within the scope of protection of the present invention, and interpreting them as any additional limitation is contrary to the spirit of the present invention.

Claims

1. A method for preparing antibacterial transparent nylon, characterized in that: The preparation method comprises the following steps: (1) adding nylon, a crosslinking agent and a catalyst to a modified cyclodextrin solution to carry out a grafting reaction to obtain cyclodextrin-grafted nylon; (2) Adding the cyclodextrin-grafted nylon into a nano-scale metal ion solution, and then filtering, washing, and drying to obtain the antibacterial transparent nylon.

2. The method for preparing antibacterial transparent nylon according to claim 1, characterized in that: In the step (1), the modified cyclodextrin solution is formed by dissolving the modified cyclodextrin in an alkaline aqueous solution; the concentration of the alkaline aqueous solution is 0.5 to 2.0 mol / L, and the concentration of the modified cyclodextrin is 0.1 to 1.0 g / mL; And / or, in the step (1), the raw materials used include the following parts by weight: 8-20 parts of modified cyclodextrin, 85-92 parts of nylon, 0.1-1 part of cross-linking agent, and 0.1-1 part of catalyst.

3. The method for preparing an antibacterial transparent nylon according to claim 1, characterized in that: In the step (1), the grafting reaction temperature is 60 to 100° C. and the time is 60 to 100 minutes.

4. The method for preparing antibacterial transparent nylon according to claim 1, characterized in that: In the step (1), the preparation method of modified cyclodextrin comprises the following steps: adding a solution of p-toluenesulfonyl chloride in acetonitrile to an alkaline solution of cyclodextrin under stirring to generate precipitation and adjust the pH, continuing stirring after the addition is completed, neutralizing the reaction solution, and evaporating the filtrate obtained by suction to obtain modified cyclodextrin.

5. The method for preparing antibacterial transparent nylon according to claim 4, characterized in that: In the preparation method of the modified cyclodextrin, the cyclodextrin includes one or more of β-cyclodextrin, hydroxylated β-cyclodextrin, α-cyclodextrin, and γ-cyclodextrin; And / or, the concentration of p-toluenesulfonyl chloride in acetonitrile is 0.1-1 mol / L. And / or, the alkaline solution of cyclodextrin is formed by dissolving cyclodextrin in a sodium hydroxide solution, the concentration of the sodium hydroxide solution is 0.5-2.0 mol / L, and the concentration of the cyclodextrin is 0.1-1.0 g / mL; and / or, the ratio of the alkaline solution of cyclodextrin to the acetonitrile solution containing p-toluenesulfonyl chloride is (8-15):1; and / or, using an alkaline solution to adjust the pH to 12-14, wherein the alkaline solution includes one or more of ammonia water, potassium hydroxide, and sodium hydroxide; and / or, continue to add dropwise for 1 to 5 hours and then continue to stir for 1 to 5 hours; And / or, an acidic solution is added to the reaction solution for neutralization, wherein the acidic solution includes one or more of hydrochloric acid, sulfuric acid, nitric acid, acetic acid, and carbonic acid.

6. The method for preparing antibacterial transparent nylon according to claim 1, characterized in that: In the step (1), the nylon includes one or more of nylon 6, nylon 66, nylon 11, nylon 12, nylon 610, nylon 612, nylon 1010 and nylon 46.

7. The method for preparing antibacterial transparent nylon according to claim 1, characterized in that: In the step (1), the cross-linking agent includes one or more of silicon dioxide, polyethylene glycol dimethacrylate, methacrylate, and ethylene glycol dimethacrylate; And / or, the catalyst includes one or more of aluminum oxide, titanium dioxide, copper oxide, iron oxide, and chromium oxide.

8. The method for preparing antibacterial transparent nylon according to claim 1, characterized in that: In the step (2), the nano-scale metal ion solution is an aqueous solution rich in nano-scale metal ions, and the concentration is (1000-8000) mg / L; And / or, the nanoscale metal ions in the nanoscale metal ion solution include nanoscale silver ions or nanoscale copper ions, and the particle size is 1 to 100 nm; And / or, the ratio of the cyclodextrin-grafted nylon to the nanoscale metal ion solution is (1-20) g: (50-1000) mL.

9. An antibacterial transparent nylon composite material, characterized in that: The antibacterial transparent nylon composite material comprises the following components in parts by weight: 90 to 100 parts of antibacterial transparent nylon prepared by the method for preparing antibacterial transparent nylon as claimed in any one of claims 1 to 8, and 1 to 10 parts of an antioxidant.

10. A method for preparing an antibacterial transparent nylon composite material as claimed in claim 9, characterized in that: The preparation method comprises the following steps: S1. Wash the antibacterial transparent nylon and dry it for later use; S2, weighing the cleaned antibacterial transparent nylon and the antioxidant and mixing them evenly to obtain a mixture; S3, feeding the mixture into a twin-screw extruder and granulating it through melt extrusion.

Citation Information

Patent Citations

  • An antibacterial enhanced nylon material and its preparation method

    CN103788645B

  • Preparation method of superfine silvered antibacterial nylon fibers

    CN111005215A

  • High-barrier antibacterial nylon composite film and preparation method thereof

    CN112318891A

  • Cyclodextrin-polyamidoamine cross-linked polymer and preparation method and application thereof

    CN102140178A

  • Antibacterial finishing method for grafting beta-cyclodextrin onto wool fabric under catalysis of laccase

    CN105951436A

Cited By

  • Antibacterial nylon / ethyl lauroyl arginate hydrochloride composite film and preparation method thereof

    CN121699386A